2021
DOI: 10.3390/su13116350
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Method for Seismic and Energy Retrofitting of Masonry Buildings

Abstract: Masonry buildings built in Italy in the 60 s and 70 s of the last century frequently require energy and seismic renovation. To this end, the use of a retrofitting technique based on a multilayer coating may be applied on the building façades in order to improve its seismic and energy performances, leading to the partial or total fulfilment of structural and energy code provisions. The coating consists of a layer of Steel Fiber Reinforced Mortar combined with thermal insulation materials to get a composite pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The concern for seismic risk and its differentiated distribution in the territorial and urban context creates asymmetries in the map of spatial and temporal disadvantages, respectively, due to the different conformations of the built heritage and to the diversified perception of risk by residents and administration [52][53][54][55][56]. Similarly, the energy issue, especially in the background of its double dimensions-the general one, concerning the reduction of the climate change effects, and the specific one, the issue of the energy-building poverty-creates further aspects of urban imbalance, triggering filtering down processes in the disadvantaged districts [57][58][59][60][61][62][63][64][65].…”
Section: Contents and Aimsmentioning
confidence: 99%
“…The concern for seismic risk and its differentiated distribution in the territorial and urban context creates asymmetries in the map of spatial and temporal disadvantages, respectively, due to the different conformations of the built heritage and to the diversified perception of risk by residents and administration [52][53][54][55][56]. Similarly, the energy issue, especially in the background of its double dimensions-the general one, concerning the reduction of the climate change effects, and the specific one, the issue of the energy-building poverty-creates further aspects of urban imbalance, triggering filtering down processes in the disadvantaged districts [57][58][59][60][61][62][63][64][65].…”
Section: Contents and Aimsmentioning
confidence: 99%
“…performance of similar systems applied on RC and masonry members [22][23][24] and proof of concept regarding the effectiveness of such solutions has been provided. 21,25 A numerical study by Gkournelos et al 23 concluded that the combined seismic and energy retrofitting of existing RC buildings can reduce seismic vulnerability and minimize the expected annual loss related to earthquake risks.…”
Section: Introductionmentioning
confidence: 99%
“…who investigated this system's applicability on masonry walls subjected to out‐of‐plane and in‐plane loading. Subsequently, several experimental and numerical studies were conducted to examine the performance of similar systems applied on RC and masonry members 22–24 and proof of concept regarding the effectiveness of such solutions has been provided 21,25 . A numerical study by Gkournelos et al 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the beam-column joint experiences a brittle shear failure. Therefore, efforts are needed to strengthen the structures that were built in the 70s and 80s for their sustainability [16][17][18][19]. Several structural strengthening methods have been proposed to withstand seismic loads.…”
Section: Introductionmentioning
confidence: 99%